2023
DOI: 10.1186/s12954-023-00763-4
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of overdose alert and response technologies: introducing the TPOM-ODART framework

Abstract: Background Opioids were implicated in approximately 88,000 fatal overdoses (OD) globally. However, in principle all opioid OD are reversible with the timely administration of naloxone hydrochloride. Despite the widespread availability of naloxone among people who use opioids (PWUO), many who suffer fatal OD use alone, without others present to administer the reversal agent. Recognising this key aspect of the challenge calls for innovations, a number of technological approaches have emerged whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 35 publications
(47 reference statements)
2
7
0
Order By: Relevance
“…Accuracy of detection was unanimously found to facilitate acceptance and was of increased importance in our findings than when implicated in other studies [21,25,27]. An inaccurate device, unable to detect an overdose and differentiate between an optimal state of being high and an overdose, would be unacceptable, cause irritation and discontinuation of device use.…”
Section: Device Level Factorsmentioning
confidence: 48%
See 4 more Smart Citations
“…Accuracy of detection was unanimously found to facilitate acceptance and was of increased importance in our findings than when implicated in other studies [21,25,27]. An inaccurate device, unable to detect an overdose and differentiate between an optimal state of being high and an overdose, would be unacceptable, cause irritation and discontinuation of device use.…”
Section: Device Level Factorsmentioning
confidence: 48%
“…However, our analysis identified that individuals of 'high risk-high benefit' faced multi-thematic barriersencompassing device, individual and environment and were therefore perceived to lack the facilities for meaningful engagement and reduced efficacy of intervention. Research in Scotland found similar results, whereby willingness to engage and individuals in high need of solutions were considered not compatible, constituting a 'readiness double bind' dilemma [25]. Readiness to accept an intervention was considered a recovery decision, echoed in part within our stage of addiction recovery subtheme.…”
Section: Person Level Factorsmentioning
confidence: 95%
See 3 more Smart Citations